Parents' economic support of young-adult children: Do socioeconomic circumstances matter? - Deborah A. Cobb-Clark; Tue Gorgens (Institute for the Study of Labor (IZA), 2012)
This paper assesses how the economic support provided by parents to young adults as they complete their education and enter the labor market is related to the family's socioeconomic circumstances. We address this issue using detailed survey data on intergenerational co-residence and financial transfers merged with nearly a decade of administrative data on the family's welfare receipt while the young person was growing up. We find that young people who experience socioeconomic disadvantage are more likely to be residentially and financially independent of their parents than are their peers growing up in more advantaged circumstances. This disparity is larger for financial transfers than for co-residence and increases as young people age. Moreover, there is a clear link between parental support and a young person's engagement in study and work which is generally stronger at age 20 than at age 18 and is often stronger for advantaged than for disadvantaged youths. We find no evidence, however, that a lack of parental support explains the socioeconomic gradient in either studying or employment.
urn:nbn:de:101:1-201206146514
Keywords: J12; J13; J22; J24; 330; co-residence; financial transfers; socioeconomic disadvantage; youth outcomes; Privater Transfer; Eltern; Kinder; Erwachsene; Familiensoziologie; Schätzung; Australien